Ultra-miniaturized dual-band implantable antenna for retinal prosthesis - Bousrout, Abdelmouttalib; Khabba, Asma; Ibnyaich, Saida; Mazri, Tomader; Habibi, Mohamed; Sutikno, Tole (Institute of Advanced Engineering and Science, 2024)
This article presents two miniaturized antennas designed for retinal prosthesis devices, aimed at enhancing vision for blind individuals with functional optic nerves. The implantable antenna is 2.2 mm wide, 2.15 mm tall, and 0.78 mm thick. It works in the ISM bands but is small because it uses slot incorporation and high-permittivity substrates. High-frequency structure simulator (HFSS) electromagnetic simulations show great performance, with a 16.66% impedance bandwidth at 2.4 GHz and a 10.34% bandwidth at 5.8 GHz. The peak gain values are -27.76 dB at 2.4 GHz and -16.40 dB at 5.8 GHz. We have also developed an extraocular antenna for telemetry and energy transfer, with dimensions of 36×36×1.6 mm3 . Validation through CST calculation software confirms the efficacy of both antenna designs. Implantable antennas hold significant promise in biomedical antenna research, demonstrating capabilities conducive to retinal implantation and offering potential advancements in vision restoration technology.